For ourselves and for each other: Politics of embodied religious belonging in the novel We Sinners - Wallenius-Korkalo, Sandra (Temenos, 2016)
This article analyses religious belonging in a Christian revivalist community through a reading of Hanna Pylväinen’s novel We Sinners, a fictive history of a Laestadian family in the modern American Midwest. Like many conservative religious groups today, Laestadianism is increasingly affected by secular society’s norms and practices. We claim that the study of everyday religious belonging is essential in order to make sense of the power relations, structures, and dynamics of change within religious groups. The article approaches belonging as a thoroughly embodied state, taking the view that certain kinds of corporeality threaten the cohesion of religious communities while others strengthen it. The politics of belonging in the novel - the practices of inclusion and exclusion - are constructed in, on, and through the regulation of individual bodies. Control over clothing, behaviour, sexuality, movement, and being-in-common produces and governs embodied Laestadian subjectivity, as well as the ways in which belonging is shared.